2020
DOI: 10.1007/s11469-019-00214-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in the UK Police Force: a Qualitative Investigation into the Stigma with Mental Illness

Abstract: Police work is a high-risk profession that can cause mental health conditions. With increasing sickness levels and falling police numbers, it is essential prompt mental health treatment be implemented. The study aims to explore institutional negativity and stigma in the police force towards mental ill health. Semi-structured interviews attended by five police officers with thematic analysis captured (i) police culture, (ii) the stigma of mental illness, (iii) disclosure of mental illness and (iv) breaking down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 63 publications
2
91
0
11
Order By: Relevance
“…A smaller, qualitative study in the UK found similar results of officers reporting stigma associated with seeking mental health care and lack of support from line management that hindered officers’ desire to disclose mental distress. 33 …”
Section: Discussionmentioning
confidence: 99%
“…A smaller, qualitative study in the UK found similar results of officers reporting stigma associated with seeking mental health care and lack of support from line management that hindered officers’ desire to disclose mental distress. 33 …”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, in a recent large-scale survey of Canadian public safety personnel, Carleton and his colleagues (2018a) found that officers screen postive for mental disorders at prevalences much higher than those seen among the general population, and screen for higher prevalances of suicide ideation and attempts (Carleton et al, 2018b). However, despite the high prevalence of mental health needs, workplace barriers continue to prevent treatment-seeking among police as well as other public safety personnel (Ricciardelli et al, 2018); these barriers include stigma, abandoning colleagues to work in increasingly understaffed conditions, and occupational repercussions (e.g., inability to promote) (Edwards and Kotera, 2020;Ricciardelli et al, 2019;Rose and Unnithan, 2015).…”
Section: Police and Mental Healthmentioning
confidence: 99%
“…All these are potential stressors in the police staff which can lead to significant mental health or psychological problems in them. There have been instances of high rates of depression, substance abuse, and suicide in the police staff (Di Nota et al 2020;Edwards and Kotera 2020). So far, only a few studies have focused on the mental/psychological consequences of perceived work stress in police officers and public safety workers during natural and human-made disasters and have reported high rates of post-traumatic stress disorder (PTSD) and depression in them (Benedek et al 2007;Gershon et al 2009).…”
mentioning
confidence: 99%